FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN ANC DI PUSKESMAS GUNUNG INTAN KABUPATEN PENAJAM PASER UTARA - Siti Amanah (Universitas Widya Gama Mahakam Samarinda, 2017)
The data of coverage number of pregnant women visit K1 and K4 in East Kalimantan province 2013 was amounted to 97.4% and 85.07%, that value has not yet reached the resentra's target in 2013 in the amount of 100% and 95%. Based of Data Health Service Penajam Paser Utara in 2014 showed Maternal Mortality Rate (MMR) in the amount of 196 per 100,000 live births. Although the K1 and K4 visit coverage that is reach to 102.5% and 89.5%, in 2015 increased to 104% and 97%. This study aimed to determine factors related to the visit Antenatal Care (ANC) in Puskesmas Gunung Intan Penajam Paser Utara on 2016. This study uses Analytical Survey by using cross sectional approach. Respondents are all pregnant women who are in working area Puskesmas Gunung Intan many as 113 respondents and a sampling technique by using purposive sampling technique. The data analysis was performed univariate and bivariate by using Chi-Square test. The results of this research obtained that all variables studied had a relationship with antenatal care (ANC) visit in Puskesmas Gunung Intan, Penajam Paser Utara in 2016, include knowledge (p value 0.001), attitude (p value 0.001) and family support (p value 0.026). The conclusion of this study is that the knowledge, attitude and family support pregnant women were able to incference visits of pregnant women to antenatal care (ANC). Thus, village midwives, the officers of Health Promotion and Nutrition needs to be increase the counseling about the importance of prenatal care to the community intensively so that their knowledge especially on pregnant women can be increased their awareness about the importance of prenatal care fully